A Legal and Psychosocial Communication Analysis to End Silence around Sexual Harassment Inside Islamic Boarding Schools - Firdaus, Dwi Rini Sovia; Aminuddin, Ahsani Taqwim; Alamsyah, Feri Ferdinan; Sariswara, Valianty; Jayawinangun, Roni; Soleha, Nadia Ismi (Udayana Journal of Law and Culture, 2025)
Sexual harassment in educational institutions has increasingly become a topic of concern worldwide, with Islamic boarding schools in Indonesia not exempt from these issues. In West Java - Indonesia, the stigma surrounding sexual harassment in pesantrens (Islamic boarding schools) presents unique challenges, deeply rooted in cultural, religious, and institutional norms. This paper investigates the factors that contribute to the stigma associated with reporting sexual harassment in pesantren, examining how it affects santris’ (students’) willingness to disclose incidents, seek support, and obtain justice. It also reveals the efforts made by the government in terms of the adoption of law and policy to address such matters. It applies a mixed-methods approach, including field observation, quantitative survey amongst santris, in-depth qualitative interviews with santri victims, and a focus group discussion with parent, psychologist, and pesantren administrator from some pesantrens in West Java. It also involves a legal approach by analysing relevant laws and regulations. The study explores the psychosocial, socio-cultural, religious, and educational dimensions perpetuating silence around harassment issues. Findings indicate that fear of damaging the school’s reputation, social retaliation, victim-blaming, and interpretations of religious principles are significant barriers to open disclosure and reporting. By addressing the stigma, this study contributes to safer, more transparent educational environments in pesantrens, ultimately empowering santri and enhancing community awareness of the need to confront and prevent sexual harassment. The paper advocates for targeted interventions, including sensitive programs, reforms in school policies, and collaborations with religious authorities to foster a supportive environment.